Effective Chromium (VI) Removal from Contaminated Water by Chemically Modified Litchi Chinensis Seed Powder: Characterization, Kinetic and Isotherm Studies - Rai, Rajan; Pokharel, Maya; Khadka, Devendra; Baral, Janaki; Paudel, Dasu Ram; Gautam, Surendra Kumar; Pokhrel, Megh Raj; Poudel, Bhoj Raj (International Journal of Environment, 2023)
In this work, Litchi chinensis seed powder has been chemically modified to charred Litchi chinensis seed powder (CLCS) for removal of Cr(VI) from the simulated wastewater. The adsorption capacity of CLCS for Cr(VI) was determined in batch experiment method. The materials were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and fourier transform infrared (FTIR) spectroscopy. Biosorption behaviour was investigated using isotherm and kinetic models. CLCS demonstrated a noteworthy adsorption capacity for Cr(VI), with a maximum adsorption capacity of 69.93 mg/g at pH 2.0. The Cr(VI) adsorption onto CLCS was found to follow pseudo-second-order kinetics and the experimental data best fitted with Langmuir isotherm model. According to the results, Cr(VI) can be removed from acidic wastewater using CLCS as an adsorbent. The results indicate that further studies and modification are necessary to improve the efficiency of the CLCS, and its feasibility at normal pH conditions.